2020
DOI: 10.7150/jca.40319
|View full text |Cite
|
Sign up to set email alerts
|

Lnc-SNHG16/miR-128 axis modulates malignant phenotype through WNT/β-catenin pathway in cervical cancer cells

Abstract: Background: The lnc-SNHG16 serves as an oncogene and miR-128 acts as a tumor suppressor in various cancers. However, the functional role of lnc-SNHG16 and miR-128 in CC still remain unknown. This study aims to explore the expression level of lnc-SNHG16 and miR-128 and its biological roles in CC. Methods: lnc-SNHG16, miR-128, GSPT1 and WNT3A expression were analyzed using quantitative real-time PCR and bioinformatics in cervical cancer tissues and cells. Cell Counting Kit-8, EdU staining, colony formation assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 40 publications
2
35
0
Order By: Relevance
“…In line with our results, Wu et al have showed that miR-128 is downregulated in CC cells, whereas up-regulation of miR-128 obviously suppresses the proliferation, migration, and invasion in CC in vitro. 22 Moreover, we also proved miR-128-3p was a target of MIR4435-2HG. The results implied that miR-128-3p might be regulated by MIR4435-2HG to inhibit the development of CC.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…In line with our results, Wu et al have showed that miR-128 is downregulated in CC cells, whereas up-regulation of miR-128 obviously suppresses the proliferation, migration, and invasion in CC in vitro. 22 Moreover, we also proved miR-128-3p was a target of MIR4435-2HG. The results implied that miR-128-3p might be regulated by MIR4435-2HG to inhibit the development of CC.…”
mentioning
confidence: 69%
“…21 In addition, miR-128 has been reported to play an anti-cancer role in CC. 22 A recent study has showed that up-regulation of miR-128 conspicuously inhibits the cell viability and epithelial-mesenchymal transition (EMT) procession in CC. 22 However, the regulatory relationship between MIR4435-2HG and miR-128-3p in CC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…miR-128 is closely involved in bone formation-related molecular and signaling pathways, such as Wnt/β-catenin (Fang et al, 2019;Roy et al, 2020;W. Wu et al, 2020), TGF-β (Cai et al, 2017), PI3K/ AKT (Guo et al, 2018;Huo et al, 2019;, AMPK/mTOR (Qi et al, 2020), PPARγ/NF-κB (Qi et al, 2020).…”
Section: Mir-128 and Osteoblastogenesismentioning
confidence: 99%
“…[26][27][28] Aberrant miRNA expression is well recognized as a cancer hallmark. It has been reported that some miRNAs involved in the progression and development of cervical cancer, including miR-128, 29 miR-30a, 30 miR-224-3p 31 and miR-186. 32,33 Considering the interaction of lncRNA and miRNA plays an important role in cancer occurrence and progression, 34 it is necessary to clarify the mechanism of lncRNA DLEU2 in cervical cancer by regulating miRNA in cervical cancer.…”
Section: Introductionmentioning
confidence: 99%